Les enjeux de la patrimonialisation du Parc naturel des Marais de Santoña, Victoria et Joyel (Cantabrie, Espagne) - Carmen Gil de Arriba (VertigO)
The Santoña, Victoria and Joyel Natural Marsh Park is one of the main wetlands and the most important ecosystem of the Spanish Cantabrian coast, due to its ecological value as a winter area for migratory birds. This natural environment, composed of three main areas, occupies more than 6,600 ha. distributed among eleven municipalities. Its conservation and planning process started in 1992 with the creation of a Nature Reserve by the State Administration. In 2007, the authority was finally transferred to the Cantabrian Autonomous Government who in turn declared this territory a Natural Park in 2006.This paper aims to study the dimensions of the conflicts experienced throughout this process, in order to understand the position taken by various opinions and interests in the decision-making of a protected area.